A gold nanoparticle-based four-color proximity immunoassay for one-step, multiplexed detection of protein biomarkers using ribonuclease H signal amplification. Issue 22 (2nd February 2018) - Xu, Jiayao; Shi, Ming; Chen, Wenting; Huang, Yong; Fang, Lina; Yao, Lifang; Zhao, Shulin; Chen, Zhen-Feng; Liang, Hong
Abstract : A gold nanoparticle-based four-color fluorescence proximity immunoassay was developed for multiplexed analysis of protein biomarkers using ribonuclease H signal amplification. Abstract : A novel gold nanoparticle-based four-color fluorescence proximity immunoassay is developed for one-step, multiplexed detection of protein biomarkers using ribonuclease H signal amplification. This assay could detect proteins with detection limits down to pg mL −1 and a 5-log dynamic range. Furthermore, it is suitable for rapid, direct quantification of multiple proteins in biological samples.